Localised alopecia: A case study - Pablo Fernandez-Crehuet; Patricia Cabeza-Calleja; Jose Luis Fernandez-Crehuet Serrano; Victoria Martinez-Prieto (Australian family physician, 2013)
A young male, 6 years of age, who had previously been well, presented with his parents to the paediatric walk-in clinic. The child was fully vaccinated, had no drug allergies and no family history of alopecia or autoimmune disease. His parents described a 3 year history of a patch of right-sided temporal hair loss, which had not changed over time. Treatment with topical corticosteroids (fluticasone propionate once per day for three months) was prescribed by the pediatrician, who reviewed the patient once per month. As there was no significant improvement after 3 months, the patient was then referred to the dermatology department. At the initial visit, he was noted to have a circumscribed 3 x 5 cm triangular plaque of alopecia on the right temporal area of the scalp (Figure 1a and 1b). There were no signs of inflammation, scaly or broken hairs, or tapering hair. His eyelashes, eyebrows and nails were all noted to be normal.